2013
DOI: 10.1016/j.jvs.2013.06.064
|View full text |Cite
|
Sign up to set email alerts
|

Shared quality data are associated with increased protamine use and reduced bleeding complications after carotid endarterectomy in the Vascular Study Group of New England

Abstract: Objective The goal of this study was to evaluate whether protamine usage after carotid endarterectomy (CEA) increased within the Vascular Study Group of New England (VSGNE) in response to studies indicating that protamine reduces bleeding complications associated with CEA without increasing the risk of stroke. Methods We reviewed 10,059 CEAs, excluding concomitant coronary bypass, performed within the VSGNE from January 2003 to July 2012. Protamine use and reoperation for bleeding were evaluated monthly usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Interestingly, our current study also confirmed that the use of protamine to reverse heparin during CEA has a powerful protective effect against reoperation for bleeding, a finding consistent with previously published studies by Patel et al 18 and Stone et al 19 In our current study, the administration of protamine to reverse heparin in patients taking dual therapy was associated with observed reoperation for bleeding rates of <1%. These findings further highlight that the optimal perioperative management of patients undergoing CEA calls for continued dual antiplatelet therapy in combination with intraoperative protamine administration.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, our current study also confirmed that the use of protamine to reverse heparin during CEA has a powerful protective effect against reoperation for bleeding, a finding consistent with previously published studies by Patel et al 18 and Stone et al 19 In our current study, the administration of protamine to reverse heparin in patients taking dual therapy was associated with observed reoperation for bleeding rates of <1%. These findings further highlight that the optimal perioperative management of patients undergoing CEA calls for continued dual antiplatelet therapy in combination with intraoperative protamine administration.…”
Section: Discussionsupporting
confidence: 92%
“…One example of a regional quality group achieving this goal is from the Vascular Study Group of New England (VSGNE), which demonstrated that a focus on protamine use during CEA in their region resulted in an increase in protamine use from 46% before 2009 to 61% after 2009. 21 Corresponding to the increase in protamine use, there was a decrease in the incidence of reoperation for bleeding from 1.2% to 0.6%, with no change in the incidence of postoperative neurologic events.…”
Section: Discussionmentioning
confidence: 94%
“…We believe this internally driven, self-monitored approach has high buy-in from participating centers and early efforts have shown it to be effective in changing practice, as reported for bovine patch use and protamine administration in the Vascular Study Group of New England. [36, 37] Future analyses focused on adherence rates to new guidelines will need to factor in the confounding effect of the addition of new hospitals to the VQI.…”
Section: Discussionmentioning
confidence: 99%